Are higher pre‐diagnosis follicle stimulating hormone levels associated with long‐term prostate cancer risk?. Issue 16 (18th August 2022) - Dymanus, Kyle; Howard, Lauren E.; Oyekunle, Taofik; De Hoedt, Amanda M.; Labadzhyan, Artak; Polascik, Thomas; Freedland, Stephen J.; Klaassen, Zachary
Abstract: Background: Follicle stimulating hormone (FSH) is a pituitary hormone that helps regulate testosterone homeostasis. Although it is generally accepted that FSH levels increase with LHRH‐agonist therapy for prostate cancer (PC), the specific impact of FSH levels on risk of PC diagnosis is largely unknown. The objective of this study was to perform a population‐level analysis to assess the association between FSH levels and PC diagnosis. Methods: All men ( n  = 386, 018) who had a pre‐PC diagnosis FSH level and complete data were identified within the Veterans Affairs Health System between 1999 and 2018. The association between FSH level and time from FSH test to PC diagnosis was tested using stratified Cox proportional hazards models. Multivariable models were adjusted for age, year, race, body mass index, and Charlson comorbidity index. Due to nonproportional hazards over time, time to PC was modeled separately: ≤4 years after an FSH test and >4 years following an FSH test. Results: Median age at first FSH level was 64 years (interquartile range [IQR]: 54–72), median year of FSH was 2010 (IQR: 2005–2014), and 70% of the cohort was white. Median follow‐up was 76 months (IQR: 38–126) during which 17, 519 men (4.5%) were diagnosed with PC. On multivariable analysis, in the first 4 years after FSH test, there was no association between FSH and time to PC diagnosis. Starting from 4 years after FSH test, on multivariable analysis, a higher FSH level was associated with lower risk of PC with continuous modeling, but found no association with log continuous and categorical modeling. Conclusions: In this population‐level study among male veterans receiving an FSH test for an unknown clinical indication, associations between FSH levels and PC risk were inconsistent and likely driven by selection bias and confounding variables. Future studies should consider different study designs.